The Values of the Qur'an in the Tradition of Beghanyut Selawat in the Perkumpulan Sholawat Laut Indonesia, Bengkalis Regency, Riau - Mujtahidah, Siti Barika; Arni, Jani; Bakar, Abu (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2023)
This article discusses the reception of the community towards the tradition of Selawat Benghanyut in the Perkumpulan Sholawat Laut Indonesia in Bengkalis Regency, Riau. The tradition of Selawat is performed by the Bengkalis community with the aim of preserving the village. The people of Bengkalis refer to it as